SAT0088 Predictive factors for interstitial lung disease progression in patients with rheumatoid arthritis: a role for biological inflammation and disease modified anti rheumatic drugs (DMARDS). (12th June 2018) - Lucas, C.; Jouneau, S.; Lederlin, M.; Guillot, S.; Salliot, C.; Joffres, L.; Solau-Gervais, E.; Herbette, M.; Saraux, A.; Cren, J.-B.; Bouvard, B.; Albert, J.-D.; et al.
Abstract : Background: Interstitial Lung Disease (ILD) related to Rheumatoid Arthritis (RA) is frequent. ILD is associated with an increased mortality in RA patients. Predictive factors for ILD progression are not well studied. Objectives: In RA patients with an ILD according to CT scan criteria, identify clinical and biological predictive factors for ILD progression. Methods: It is a retrospective multicentric study. RA patients with ILD confirmed by a first thoracic CT scan (tCT at T0) were included if ILD progression could be studied with a second CT scan (Tx) done at least 6 months after T0. RA patients were classified in two groups after double tCT evaluation on a blind review of data: those with ILD progression (pILD) and those with a stable ILD (sILD). Predictive factors for tCT ILD progression were studied by comparing these two groups. Studied data were ILD pattern, classified into typical UIP (Usual Interstitial Pneumonia) or not typical UIP, RA disease characteristics, biological parameters, and RA treatments, collected for each patient at T0 and Tx. Results: Thirty-six RA patients with ILD confirmed by tCT were included. During an average follow-up of 3 years, 21 RA patients (58.1%) had ILD progression. Predictive factors for ILD progression a T0 are shown in table 1. In pILD group, we observed a significant higher value of the C Reactive Protein (CRP). A CRP rate superior to 20 mg/L was highly associated to ILD progression (Odds ratio=14.4; IC95%(1.36–15.2); p=0.02). Eight patients were treated at T0 by a DMARD different from Methotrexate (MTX). They all were in pILD group (p=0.01). Thirteen patients were treated with MTX at T0. Eight of them were in sILD group (61.5%) and only 5 patients in pILD group (38.5%). Eight patients continued MTX treatment after ILD diagnosis and for one patient, MTX was introduced between T0 and TX. For these 9 patients exposed to MTX after ILD diagnosis, during 27 months on average, no significant ILD progression was observed. Conclusions: Factors associated with ILD progression were biological inflammation and exposure to a DMARD different from MTX. Exposure to MTX before or after ILD diagnosis was not associated with ILD worsening during the follow up. Disclosure of Interest: None declared